Advances in the study of subclinical AKI biomarkers - Zou, Chenchen; Wang, Chentong; Lu, Lin (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a common and critical condition in all clinical departments, with high morbidity and mortality, especially in intensive care units, where prevention and treatment are critical. Therefore, active prevention, early recognition and timely intervention for acute kidney injury are particularly important. Currently, the diagnostic criteria for acute kidney injury are based on an increase in serum creatinine concentration and/or a decrease in urine output, but creatinine and urine output only reflect changes in kidney function, and AKI implies injury or damage, but not necessarily dysfunction. The human kidney has an important functional reserve role and dysfunction only becomes apparent when more than 50% of the kidney mass is compromised. It is possible to use markers of tubular damage to diagnose AKI early before the loss of filtration function, and new biomarkers have revealed a new subgroup of AKI patients called "subclinical AKI". Moreover, creatinine and urine volume have limited ability to identify subclinical AKI. Therefore, the search for new biomarkers not only shows deterioration of renal function but also allows early identification of structural kidney damage. A number of biomarkers have been identified and validated, and this paper describes some of the most promising novel biomarkers of AKI, including CysC, NGAL, KIM-1, lL-18, L-FABP, IGFBP7, TIMP-2, Clusterin, and Penkid. we discuss their performance in the diagnosis of subclinical AKI, their current We discuss their performance in the diagnosis of subclinical AKI, their current limitations, and future directions in clinical practice.